2019
DOI: 10.14814/phy2.13952
|View full text |Cite
|
Sign up to set email alerts
|

FURINvariant associations with postexercise hypotension are intensity and race dependent

Abstract: FURIN is a proprotein convertase subtilisin/kexin enzyme important in pro‐renin receptor processing, and FURIN (furin, paired basic amino acid cleaving enzyme) variants are involved in multiple aspects of blood pressure (BP) regulation. Therefore, we examined associations among FURIN variants and the immediate blood pressure (BP) response to bouts of aerobic exercise, termed postexercise hypotension (PEH). Obese (30.9 ± 3.6 kg m−2) Black‐ (n = 14) and White‐ (n = 9) adults 42.0 ± 9.8 year with hypertension (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
(92 reference statements)
0
9
0
2
Order By: Relevance
“…Of the qualifying trials containing human genes in major BP regulatory pathways, we extracted 11 genes associated with the BP response to exercise under criteria 1 [33,34,35,36,37,38,39,40]; 18 genes associated with hypertension in GWAS under criteria 2 [41,42,43,44,45,46,47,48]; 28 genes associated with the BP response to pharmacotherapy under criteria 3 [49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]; 27 genes associated with physical activity and/or obesity in GWAS under criteria 4a [71,72,73,74,75,76,77,78,79,80,81,82,83,84,85]; and 29 genes associated with BP, physical activity, and/or obesity in non-GWAS under criteria 4b [86,87,88] displayed in Supplemental Digital Content (SDC) 1 Table S1. In addition, we included the 41 genes from our preliminary work that were reported to be associated with hypertension or the BP response to exercise or pharmacotherapy [27,28,29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the qualifying trials containing human genes in major BP regulatory pathways, we extracted 11 genes associated with the BP response to exercise under criteria 1 [33,34,35,36,37,38,39,40]; 18 genes associated with hypertension in GWAS under criteria 2 [41,42,43,44,45,46,47,48]; 28 genes associated with the BP response to pharmacotherapy under criteria 3 [49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]; 27 genes associated with physical activity and/or obesity in GWAS under criteria 4a [71,72,73,74,75,76,77,78,79,80,81,82,83,84,85]; and 29 genes associated with BP, physical activity, and/or obesity in non-GWAS under criteria 4b [86,87,88] displayed in Supplemental Digital Content (SDC) 1 Table S1. In addition, we included the 41 genes from our preliminary work that were reported to be associated with hypertension or the BP response to exercise or pharmacotherapy [27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, using newer genomic technology that emerged since our discovery phase candidate gene association studies, in a replication cohort we deep-sequenced the exons of genes contained on a prioritized signature of 41 genes identified from our earlier work combined with those from a systematic review of the literature of genes reported to be associated with hypertension or the BP response to exercise or pharmacotherapy using the Illumina TruSeq Custom Amplicon kit [27,28,29]. Even after adjustment for multiple testing, we found that 61% of the genes in the prioritized panel associated with the BP response to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations